Microarray profiling of hypothalamic gene expression changes in Huntington’s disease mouse models - Dickson, Elna; Dwijesha, Amoolya Sai; Andersson, Natalie; Lundh, Sofia; Björkqvist, Maria; Petersén, Åsa; Soylu-Kucharz, Rana (Frontiers in Neuroscience, 2022)
Structural changes and neuropathology in the hypothalamus have been suggested to contribute to the non-motor manifestations of Huntington’s disease (HD), a neurodegenerative disorder caused by an expanded cytosine-adenine-guanine (CAG) repeat in the huntingtin (HTT) gene. In this study, we investigated whether hypothalamic HTT expression causes transcriptional changes. Hypothalamic RNA was isolated from two different HD mouse models and their littermate controls; BACHD mice with ubiquitous expression of full-length mutant HTT (mHTT) and wild-type mice with targeted hypothalamic overexpression of either wild-type HTT (wtHTT) or mHTT fragments. The mHTT and wtHTT groups showed the highest number of differentially expressed genes compared to the BACHD mouse model. Gene Set Enrichment Analysis (GSEA) with leading-edge analysis showed that suppressed sterol- and cholesterol metabolism were shared between hypothalamic wtHTT and mHTT overexpression. Most distinctive for mHTT overexpression was the suppression of neuroendocrine networks, in which qRT-PCR validation confirmed significant downregulation of neuropeptides with roles in feeding behavior; hypocretin neuropeptide precursor (Hcrt), tachykinin receptor 3 (Tacr3), cocaine and amphetamine-regulated transcript (Cart) and catecholamine-related biological processes; dopa decarboxylase (Ddc), histidine decarboxylase (Hdc), tyrosine hydroxylase (Th), and vasoactive intestinal peptide (Vip). In BACHD mice, few hypothalamic genes were differentially expressed compared to age-matched WT controls. However, GSEA indicated an enrichment of inflammatory- and gonadotropin-related processes at 10 months. In conclusion, we show that both wtHTT and mHTT overexpression change hypothalamic transcriptome profile, specifically mHTT, altering neuroendocrine circuits. In contrast, the ubiquitous expression of full-length mHTT in the BACHD hypothalamus moderately affects the transcriptomic profile.